Finding Meaning in Late Adulthood: A Qualitative Study on Subjective Well-Being among Childless Elderly - Afifah, Hana Rifda; Muntafi, Muhammad Syifaul (International Conference on Sustainable Health Promotion, 2025)
The purpose of this study is to describe subjective well-being in older adults without children using a phenomenological qualitative approach. The study participants consisted of two women aged 68 and 71 years who were selected through purposive sampling. Data were collected through semi-structured interviews and analyzed using thematic methods. The results showed that subjective well-being in elderly people without children was reflected in six cognitive themes, namely life satisfaction, spirituality, social relationships, productive activities, physical and mental health, and material sufficiency, as well as two affective themes, namely positive affect and negative affect. The elderly define happiness through harmonious relationships with their spouses, fostering children, spiritual activities, and involvement in social and productive activities. Positive affect, such as gratitude and happiness, is more dominant than negative affect, such as anxiety and loneliness, which are managed through social support and meaningful activities. These findings emphasize the importance of social support, spirituality, and meaningful activities in improving the quality of life of older adults without children.